2021
DOI: 10.1038/s41598-021-91593-6
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine delivery and relief of craving after consumption of European JUUL e-cigarettes prior and after pod modification

Abstract: The emergence of e-cigarettes on the consumer market led to a tremendous rise in e-cigarette consumption among adolescents in the United States. The success of JUUL and other pod systems was linked to its high nicotine delivery capacity. In compliance with the European Tobacco Product directive, liquid nicotine contents in the European JUUL variants are limited to 20 mg/mL or below. A short time after launching the initial version in Europe, JUUL pods have been modified in terms of the wick material used. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…The addictiveness of tobacco products depends both on the nicotine dose and the rapidity of nicotine delivery. In Europe, the limitation of nicotine to 20 mg/mL imposed by the European Tobacco Product Directive may mitigate the craving satisfaction experienced by users for nicotine content superior to 18 mg/mL but also may suggest a lower addiction potential. , Still, nicotine salts may considerably modify nicotine pharmacokinetics, thus addictiveness, even at lower doses through other mechanisms such as (1) a change of nicotine cellular uptake induced by protonated form compared to free-base form, (2) a modification in the gas/particle repartition of nicotine in the aerosol because the gaseous state or dissolved in a droplet of nicotine is a possible important factor of nicotine pharmacokinetics, and (3) the throat hit suppression/reduction enable deeper lung inhalation of the aerosol and a better aerosol deposition in the alveolar region favoring a more rapid or greater systemic passage. Additionally, NicH + could directly impact lung biological integrity.…”
Section: Introductionmentioning
confidence: 99%
“…The addictiveness of tobacco products depends both on the nicotine dose and the rapidity of nicotine delivery. In Europe, the limitation of nicotine to 20 mg/mL imposed by the European Tobacco Product Directive may mitigate the craving satisfaction experienced by users for nicotine content superior to 18 mg/mL but also may suggest a lower addiction potential. , Still, nicotine salts may considerably modify nicotine pharmacokinetics, thus addictiveness, even at lower doses through other mechanisms such as (1) a change of nicotine cellular uptake induced by protonated form compared to free-base form, (2) a modification in the gas/particle repartition of nicotine in the aerosol because the gaseous state or dissolved in a droplet of nicotine is a possible important factor of nicotine pharmacokinetics, and (3) the throat hit suppression/reduction enable deeper lung inhalation of the aerosol and a better aerosol deposition in the alveolar region favoring a more rapid or greater systemic passage. Additionally, NicH + could directly impact lung biological integrity.…”
Section: Introductionmentioning
confidence: 99%
“…Baseline characteristics for all 32 participants are presented in Table 1 and the flow of participants through the study is shown in Figure 1. The nicotine levels for the three groups with the corresponding numbers of participants are shown in Figure 2 36 .…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…Reasons for this were discussed and include the social media marketing strategy, the selection of appealing flavors, product features, and the high nicotine delivery of the US version [ 16 , 17 , 18 , 19 , 20 ]. While we have showed that the European version delivers much less nicotine than a conventional cigarette in a study applying a pre-directed puffing protocol [ 21 ], it is unclear what nicotine levels are reached when consumers use the products in their own pattern. It was hypothesized that pod e-cigs may be used differently than known for older generation e-cigs.…”
Section: Introductionmentioning
confidence: 99%